2020
DOI: 10.26553/jikm.2020.11.1.75-88
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Working Postures with Musculoskeletal Disorders (Msds) Complaint of Tailors in Ulak Kerbau Baru Village, Ogan Ilir

Abstract: Tailor is one of the professions that has MSDs risk. It is because of the working posture, such as sitting for a long time and repetitive movements. The purpose of this study is to determine correlation between working postures and Musculoskeletal Disordes (MSDs) of Tailors in Ulak Kerbau Baru Village Ogan Ilir. This research was an cross-sectional and method of sampling in this study was using accident sampling with sample were 75 respondents. Rapid Entire Body Assessment (REBA) method was used assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 13 publications
1
3
0
8
Order By: Relevance
“…Therefore, to decrease the risk of MSD complaints, the sewing workers were suggested to pay more attention to their physical condition, such as by working out since the increase of age tends to lower the individual's physical strength. [7] A correlation between gender and MSD complaints (p-value = 0.049) was found in this research. Several studies have shown a relationship between gender and musculoskeletal disorders.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, to decrease the risk of MSD complaints, the sewing workers were suggested to pay more attention to their physical condition, such as by working out since the increase of age tends to lower the individual's physical strength. [7] A correlation between gender and MSD complaints (p-value = 0.049) was found in this research. Several studies have shown a relationship between gender and musculoskeletal disorders.…”
Section: Resultssupporting
confidence: 62%
“…Doing awkward positions for hours in a day can also lead to muscle fatigue and stress because the body position tends to be the same as doing repetitive activities. [7] Research by Putri (2022) showed that based on the research on the working posture using the ROSA method, it was found that 4 of 6 Batam City Environmental Office workers scored more than 5, which meant that the workers' working postures were at risk. Muscle complaints (MSD) and the risky working posture indicated that improvement measures were needed.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1, visualization of Musculoskeletal Disorders (MSDs) Cobblers complaints with the highest pain complaint rate of 50%. The findings of Hutabarat [6], Andriani et al [7], Szczygieł et al [8], and Zein et al [9] proved that work activity in sitting conditions has a high level of musculosceletal disorders due to muscle tension. It is mentioned that the need for interlude activities such as rest by standing to straighten the condition of the back [10].…”
Section: Figure 1 Complaint Rate Of Musculoskeletal Disorders (Msds) ...mentioning
confidence: 96%
“…Tercatat prevalensi Gangguan musculoskeletal secara global berada pada rentang 14%-42%. 9 Angka kejadian ini terus meningkat sejak 2012. Berdasarkan jumlah kejadian yang dilaporkan, diketahui sebanyak 32% merupakan kasus cedera musculoskeletal yang diakibatkan dari aktivitas kerja.…”
Section: Pendahuluanunclassified
“…Selain itu, posisi statis juga mengakibatkan penumpukan sisa meabolisme seperti asam laktat akibat terganggunya aliran darah. 9 Nilai kekuatan hubungan dalam penelitian ini lemah, hal tersebut dipicu oleh beban yang kerja yang diambil masih tergolong ringan. Keluhan akan muncul dan semakin meningkat ketika otot menerima beban berlebih secara terus menerus dan dalam durasi lama.…”
Section: Hubungan Postur Kerja Dengan Kejadian Msdsunclassified